Aminoguanidine Improved Liver Function and Attenuated Oxidative Stress in Hypothyroid Rats by Propylthiouracil - Seyed Hamidreza Rastegar-Moghaddam; Zahra Kiumarsi; Alireza Mirani; Mahdieh Mortazavi; Farimah Beheshti; Alireza Ebrahimzadeh-Bideskan; Akbar Anaeigoudari; Mahmoud Hosseini (Advanced Biomedical Research)
Background: Hypothyroidism negatively affects liver function, which might be due to nitric oxide (NO) overproduction, oxidative stress, and fibrosis. Aminoguanidine (AMG) as an inducible NO synthase (iNOS) inhibitor attenuates NO and shows antioxidant effects. This study aimed to evaluate the protective effect of AMG against liver damage caused by hypothyroidism. Materials and Methods: The rats were divided into 5 groups and treated by (1) vehicle, (2) propylthiouracil (PTU, 0.05% in drinking water) to induce hypothyroidism, (3–5) PTU + AMG (10 mg/kg), PTU + AMG (20 mg/kg), and PTU + AMG (30 mg/kg). The rats were given AMG intraperitoneally for 6 weeks. The blood concentration of T4, alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALK-P), albumin, and total protein was estimated. The hepatic level of malondialdehyde (MDA), total thiol group, superoxide dismutase (SOD), and catalase (CAT) was also measured. In addition, liver fibrosis was evaluated using Masson’s trichrome method. Results: Hypothyroidism induced by PTU elevated the concentration of MDA, ALT, AST, and ALK-P (P < 0.001) and lowered T4, total thiol, albumin, and total protein level and SOD, and CAT activity (P < 0.001). Treatment by AMG significantly attenuated the PTU-induced hypothyroidism impact on liver functional markers and oxidative stress parameters. Accordance to the histological results, hypothyroidism enhanced fibrosis in liver tissue compared with control (P < 0.001). Injection of 30 mg/kg of AMG decreased fibrous tissue versus the PTU group (P < 0.001). Conclusion: The results suggest that AMG effectively ameliorates liver fibrosis and functional impairment resulting from hypothyroidism by reinforcing the antioxidative potential.